Addressing the quantitative skill shortage in the social sciences - Cotterell, Gerard; von Randow, Martin (New Zealand Science Review, 2010)
​Increasingly social science graduates in New Zealand, especially those in the subject areas of sociology and political studies, are graduating without essential skills in the area of quantitative data analysis. In an attempt to address these issues, the research team at the Centre of Methods and Policy Application in the Social Sciences (COMPASS) at the University of Auckland have developed two initiatives. The first of these, the New Zealand Social Statistics Network (www.nzssn.org.nz) organises short courses in research methods training. The second, the New Zealand Social Science Data Service (www.nzssds.org.nz), provides secondary data for analysis and teaching resources linked to quantitative research methods.